A Paradigm Shift in School Architecture: Flexible Spaces in Rural Schools; [Un Cambio de Paradigma en la Arquitectura Escolar: Espacios Flexibles en Escuelas Rurales] - Ipinza-Olatte, C (Universidad Austral de Chile, 2024)
/The integration of flexibility in educational spaces arises from the need to adapt the physical learning environment to the requirements of the pedagogical transformation of the 21st century. The goal is to develop a methodology to evaluate flexibility in educational spaces. In this case, eight rural schools are assessed in the Araucanía region of Chile; their designs address changes in educational paradigms, since their educational spaces were conceived for different learning modalities. An analysis methodology was developed that evaluates the architectural intentions that contribute to flexibility of use and spatial flexibility. The results suggest that the integration of design criteria has been efficient in the areas of spatial proportion, multifunctionality of use and convertibility of the spaces. However, the introduction of furniture and flexible elements to promote space adaptation was identified as a need. Finally, the importance of further investigating design aspects and use of educational spaces that support emerging didactic approaches is discussed. © (2024), (Universidad Austral de Chile). All rights reserved.